CERVICAL ADENOCARCINOMA AND THERAPEUTIC DROPOUTS: THE PERSPECTIVE OF NURSES IN A CITY IN THE EXTREME NORTH OF BRAZIL - Lima, Stanley José Moreira; Prudêncio, Luzilena de Sousa; Tostes, Nádia Cecilia Barros; Mata, Nely Dayse Santos da (Cogitare Enfermagem, 2022)
Objective: to describe, from the perspective of nurses, the causes of dropout of users in treatment for cervical adenocarcinoma and analyze the proposals to reduce this dropout. Method: the study is descriptive, qualitative, of narrative research type. Seven care nurses, working in a high complexity oncology unit in the city of Macapá, capital of the state of Amapá, Brazil, participated. The study was conducted in the period from December three to 20, 2019. Data were submitted to categorical thematic analysis. Results: two categories emerged: main causes of dropout of users in treatment for cervical adenocarcinoma and nurse strategies for the reduction of treatment dropout by users. Conclusion: to promote the rescue of the users, the participating nurses propose a Nursing consultation and a multi-professional action plan, respecting the singularities of each woman.